Electron microscopic study showing antibody-independent binding of C1q, a subcomponent of the first component of complement, to serum-sensitive salmonellae. - Clas, F (1984)
Effective serum-mediated killing of sensitive gram-negative bacteria requires all the complement components. In the preimmune phase the antibody-independent interaction of the first component of complement, C1, with the bacteria might be especially important. Electron microscopic studies showed that the C1 subcomponent C1q binds only to the serum-sensitive R form of Salmonella minnesota and not to the serum-resistant S form.